Kepribadian Big Five terhadap Impulsive Buying Behavior pada Mahasiswi Fakultas Ekonomi dan Bisnis - Putri Puji Astutik; Tutut Chusniyah; Diantini Ida Viatrie (Islamic Psychology Department, Dakwah Faculty of Universitas Islam Tribakti Lirboyo Kediri, 2020)
College students are individuals who enter the transition from adolescence to adulthood. In this period, they have more opportunities to explore various values and lifestyles. Individuals are looking for experiences that will eventually form personalities. Personality can influence individuals who make risky decisions. Decision-making immediately without prior consideration can make them behave impulsively without thinking about the effect. This study aims to determine the effect of big five personalities on impulsive buying behavior on students of the Faculty of Economics and Business, Airlangga University, Surabaya. This study uses a quantitative approach, the collected data were analyzed using multiple linear regression. Based on the analysis results obtained three conclusions, 1) Most of the students of economics and business at Airlangga University Surabaya have big five personalities that tend to be dominant; 2) Most of the economics and business students of Airlangga University Surabaya have low impulsive buying behavior; 3) Big five personality influences impulsive buying behavior in economics and business students of Airlangga University Surabaya, conscientiousness has a greater influence than extraversion, agreeableness, neuroticism, and openness to experience.